Evaluation of the suitability of cassava and sweetpotato flours for pasta production - Baah, F.D.; Oduro, I.; Ellis, W.O. (African Journals Online, 2005)
The study was carried out to establish the proportions of cassava and sweetpotato flours that would produce good quality pasta, in composite with wheat flour. Up to 50% sweetpotato and cassava flour substitutions were made. Two varieties each of cassava (Abasafitaa and Afisiafi) and sweetpotato (Faara and Sauti) were used. The following parameters were investigated on the flours: starch yield, moisture, ash, fibre, protein, amylose content, water binding capacity, swelling power, solubility, viscosity and pH. Sensory evaluation was conducted to assess the preference of the pasta products. The results showed that water binding capacity, solubility and swelling power affect the overall quality of pasta. Pasta made from sweetpotato composite flour was too brittle and crumbled easily when pressed between the fingers. Pasta made from 50% cassava (Abasafita)/50% hard wheat performed better and showed no significant difference from that made from 100% hard wheat flour.